Gasification Prospective of Compressed Industrial Tea (Camellia sinensis) Waste using Fixed Bed Downdraft Gasifier - Kumar, Sonu; Pranav, P. K. (Journal of Agricultural Engineering, 2018)
India is the second largest producer of tea in the world. Assam contributes 53 % of total plantation area and 54 % of total production of the country. Large quantity of waste is generated from tea processing which has negligible economic value. Industrial tea waste was collected from a nearby tea industry and converted into briquette after mixing with binding material. Briquette’s characteristics prepared from industrial tea waste (ITW) was found good for gasification. The calorific value of ITW was measured as 18.01 MJ.kg-1. Gasification was carried out at air flow rates of 25.32, 31.65, 34.08, and 42.96 Nm3.h-1 at four inlet settings of the blower. The producer gas composition (CO = 18.7 % and H2 =15.5 %) was highest at 31.65 Nm3.h-1 air flow rate. Maximum combustible gas discharge was 0.78 Nm3.kg-1 at air flow of 31.65 Nm3.h-1 and feed rate of 14.30 kg.h-1. Measured and estimated calorific value of the producer gas was 4.10 and 4.63 MJ.Nm-3, respectively, with 54.55 % gasification efficiency. It was concluded that ITW has good gasification potential, and may be utilised by the tea industry for partial independence from use of conventional sources of energy.